2010
DOI: 10.1111/j.1471-0528.2010.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of delivery in pregnancies with pre-existing hypertension

Abstract: Objective To determine the optimal timing of delivery in pregnancies with pre-existing (chronic) hypertension by quantifying the gestational age-specific risks of stillbirth associated with ongoing pregnancy and the gestational age-specific risks of neonatal mortality or serious neonatal morbidity following the induction of labour.Design Population-based cohort study.Setting USA.Population A total of 171 669 singleton births to women with pre-existing hypertension between 1995 and 2005. Pregnancies additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…37 In a recent study of 171 000 women with chronic hypertension, the risk of fetal death increased from gestational week 38 (1.1 per 1000 ongoing pregnancies) to week 41 (3.5 per 1000). 35 In our study, the risk of fetal death was increased in pregnancies with hypertension relative to normotensive women. The proportion of offspring that was stillborn was highest in early pregnancy, as intrauterine fetal death is an important reason for preterm induction and very preterm offspring may not survive birth because of immaturity.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…37 In a recent study of 171 000 women with chronic hypertension, the risk of fetal death increased from gestational week 38 (1.1 per 1000 ongoing pregnancies) to week 41 (3.5 per 1000). 35 In our study, the risk of fetal death was increased in pregnancies with hypertension relative to normotensive women. The proportion of offspring that was stillborn was highest in early pregnancy, as intrauterine fetal death is an important reason for preterm induction and very preterm offspring may not survive birth because of immaturity.…”
Section: Discussionmentioning
confidence: 67%
“…26,34 Population studies on the association of hypertension with fetal death from the USA have been published, but discrimination between types of hypertension in pregnancy could not be made. 1,16,35 One of these studies reported changes from 1990-1991 to 2003-04, and found an increase in pregnancy-induced hypertension (from 3 to 3.8%) and a decrease in stillbirth rate (from 6.1 to 4.8 per 1000 births) after 24 weeks of gestation. 1 However, the odds ratio of fetal death associated with hypertension increased between the two study periods from 1.37 to 1.52.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension often leads to iatrogenic pre-term delivery, intrauterine growth retardation and caesarean section. Studies indicate that in the absence of additional complications, delivery between 38 and 39 weeks of gestation compensates for the risk of maternal and neonatal complications [38,39]. Early delivery should be considered in cases of ineffective antihypertensive therapy or intrauterine growth retardation.…”
Section: A Pregnancy Complicated By Hypertensionmentioning
confidence: 99%
“…A cohort study of women with CHTN found that delivery at 38 to 39 weeks gestation was optimal for balancing fetal and neonatal risks. 35 The ACOG endorses delivery at 38 to 39 weeks for women with CHTN not requiring medication, 37 to 39 weeks for women controlled with medication, and 36 to 37 weeks for women with severe uncontrolled hypertension. 36 A randomized, controlled trial in women with either GHTN or preeclampsia without severe features found that induction of labor at 37 weeks gestation was associated with a significant decrease in composite maternal morbidity as compared with expectant management.…”
Section: Delivery Planningmentioning
confidence: 99%